Methodological considerations for blood flow restricted resistance exercise - Fahs, C. A.; Loenneke, J. P.; Rossow, L. M.; Tiebaud, R. S.; Bemben, M. G. (Journal of Trainology, 2012)
Blood flow restricted (BFR) resistance exercise has become a popular area of research. However, studies use a range of blood flow restriction and resistance exercise protocols. Objectives: To provide an overview of the methods used for BFR resistance exercise for individuals interested in utilizing BFR training and for researchers studying the acute and chronic effects of BFR resistance exercise. Design: A systematic review. Method: BFR resistance training studies with muscular strength and hypertrophy as main outcomes were identified. Resistance exercise protocol and blood flow restriction protocol were compared between these studies. Acute BFR resistance exercise studies comparing different BFR protocols were also examined. Results: Continuous, partial arterial blood flow restriction during resistance exercise appears to be tolerable and effective for increasing both limb and trunk muscle strength and hypertrophy. Compared to non-BFR exercise, blood flow restriction produces an additive effect when combined with resistance exercise loads of <50% one-repetition maximum. Optimal BFR resistance training frequency may be higher (2x daily) than high-load resistance exercise. Conclusions: Restrictive cuff size, pressure, and limb circumference affect the degree of blood flow restriction and should be carefully considered when performing or prescribing BFR resistance exercise. The volume and frequency of BFR resistance exercise may depend on the trainee's capabilities and goals.